Antibiofilm effect of melittin alone and in combination with conventional antibiotics toward strong biofilm of MDR-MRSA and -Pseudomonas aeruginosa - Mirzaei, Rasoul; Esmaeili Gouvarchin Ghaleh, Hadi; Ranjbar, Reza (Frontiers in Microbiology, 2023)
Multidrug-resistant (MDR) pathogens are being recognized as a critical threat to human health if they can form biofilm and, in this sense, biofilm-forming MDR-methicillin resistant Staphylococcus aureus (MRSA) and-Pseudomonas aeruginosa strains are a worse concern. Hence, a growing body of documents has introduced antimicrobial peptides (AMPs) as a substitute candidate for conventional antimicrobial agents against drug-resistant and biofilm-associated infections. We evaluated melittin's antibacterial and antibiofilm activity alone and/or in combination with gentamicin, ciprofloxacin, rifampin, and vancomycin on biofilm-forming MDR-P. aeruginosa and MDR-MRSA strains. Antibacterial tests (antibiogram, minimum inhibitory concentration (MIC), and minimum bactericidal concentration (MBC)), anti-biofilm tests (minimum biofilm inhibition concentration (MBIC), and minimum biofilm eradication concentration (MBEC)), as well as synergistic antibiofilm activity of melittin and antibiotics, were performed. Besides, the influence of melittin alone on the biofilm encoding genes and the cytotoxicity and hemolytic effects of melittin were examined. MIC, MBC, MBIC, and MBEC indices for melittin were in the range of 0.625–5, 1.25-10, 2.5-20, and 10–40 µg/mL, respectively. The findings found that the combination of melittin AMP with antibiotics was synergistic and fractional biofilm inhibitory concentration index (FBICi) for most tested concentrations was <0.5, resulting in a significant reduction in melittin, gentamicin, ciprofloxacin, vancomycin, and rifampin concentrations by 2–256.4, 2–128, 2-16, 4-64 and 4–8 folds, respectively. This phenomenon reduced the toxicity of melittin, whereby its synergist concentration required for biofilm inhibition did not show cytotoxicity and hemolytic activity. Our findings found that melittin decreased the expression of icaA in S. aureus and LasR in P. aeruginosa genes from 0.1 to 4.11 fold for icaA, and 0.11 to 3.7 fold for LasR, respectively. Overall, the results obtained from our study show that melittin alone is effective against the strong biofilm of MDR pathogens and also offers sound synergistic effects with antibiotics without toxicity. Hence, combining melittin and antibiotics can be a potential candidate for further evaluation of in vivo infections by MDR pathogens.